2022
DOI: 10.1101/2022.06.14.495661
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Condensin I folds theC. elegansgenome

Abstract: Structural Maintenance of Chromosomes (SMC) complexes, cohesin and condensins, were named for their roles in meiotic and mitotic chromosome separation and compaction. Recent data from mammalian cells and Drosophila have described additional roles for cohesin in folding the interphase genome into loops and domains. However, determinants of genome folding in holocentric species remain unclear. Using high-resolution chromosome conformation capture, we show that C. elegans chromosomes exhibit two types of compartm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 126 publications
0
10
0
Order By: Relevance
“…ln simulation, one-sided LEFs cannot form corner-peaks due to high frequency of gaps between two oppositely oriented LEFs [70]. This is unlikely to be a limitation in our system, because (i) in simulation, the corner-peaks can be ‘rescued’ with strong preferential loading at the boundary, and (ii) a recent preprint reported that the cleavage of DPY-26, a kleisin subunit shared by condensin l and DC, did not eliminate rex-rex corner-peaks [74]. Therefore, the corner-peak does not necessitate an explanation based on loop extrusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ln simulation, one-sided LEFs cannot form corner-peaks due to high frequency of gaps between two oppositely oriented LEFs [70]. This is unlikely to be a limitation in our system, because (i) in simulation, the corner-peaks can be ‘rescued’ with strong preferential loading at the boundary, and (ii) a recent preprint reported that the cleavage of DPY-26, a kleisin subunit shared by condensin l and DC, did not eliminate rex-rex corner-peaks [74]. Therefore, the corner-peak does not necessitate an explanation based on loop extrusion.…”
Section: Discussionmentioning
confidence: 99%
“…In mixed stage embryos and L3 worms we may be analyzing a maintenance/equilibrium state of X-chromosome organization. Hi-C data in a recent preprint presented that upon degradation of SDC-3 or cleavage of kleisin subunit DPY-26 TADs disappear but the rex-rex corner-peaks remain unperturbed [74]. This is in contrast to the genetic loss of SDC-2 resulting in the complete loss of all features of TADs [40, 55].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, facultative heterochromatin, which contains repressed genes, was at the time found together with euchromatin in the A compartment. This organisation in two compartments is conserved in multi-cellular eukaryotes, including plants [8] and species with holocentric chromosomes [7]. Principal features of chromatin compartmentalisation were later on shown to correlate with replication timing[24], TE content [5] and many other epigenetic marks [26].…”
Section: Introductionmentioning
confidence: 99%
“…Aiming to explain pattern of contacts of S domains we turned to loop extrusion, a mechanism of chromosome organization seen across species, including holocentric nematodes 19,29 . In vertebrates, loop extrusion by the SMC complex cohesin, when occluded by extrusion boundaries, generates domains of local compaction, TADs.…”
Section: Resultsmentioning
confidence: 99%
“…Many Hi-C datasets have been generated to aid genome assembly [14][15][16][17][18] , but in-depth analyses of 3D genome organization have been performed only for model organisms, including mammals, flies, nematodes, yeasts, bacteria and plants [4][5][6][7][8][9][10][11][12][13][19][20][21][22] . A recent comparison of diverse organisms provided insights into differences in genome organization.…”
Section: Introductionmentioning
confidence: 99%